Synergistic effects of hybrid nanofillers on graphene oxide reinforced epoxy coating on corrosion resistance and fire retardancy - Siti Maznah, Kabeb; Azman, Hassan; Faiz, Ahmad; Zurina, Mohamad; Zalilah, Sharer; Munirah, Mokhtar (Wiley, 2021)
This study investigated the synergistic effects of two different type of nanofillers, that is, halloysite nanotube (HNT) and montmorillonite (MMT) on anticorrosion performance and flame retardancy properties of graphene oxide reinforced epoxy coatings for structural steel application. Electrochemical impedance spectroscopy (EIS), Tafel polarization, salt spray test (SST) and limiting oxygen index (LOI) tests were conducted to reveal the effects of hybrid nanofillers on corrosion protection and flame retardancy performance of the coatings. The dispersion of the nanofillers with the matrix was characterized via transmission electron microscopy (TEM). The results showed, EGO0.6 coatings exhibited the best anticorrosion performance (Rct = 2.105 × 109 Ω.cm) compared to E0 coating (Rct = 6.420 × 108 Ω.cm) and epoxy filled with single nanofiller. The coating reinforced with hybrid nanofillers, EGO0.6H0.3 showed further improvement in corrosion resistance, compared to other single and hybrid nanofillers coatings studied. All epoxy coating samples filled with nanofillers showed slow burning behavior in the LOI test. The incorporation of hybrid nanofillers increased the LOI value of EGO0.6H0.4 coating up to 25.0 from 21.0 for neat epoxy coating. The LOI data shows a good correlation with char formation from thermogravimetric analysis analysis. TEM results revealed a positive effect of the nanofillers on HNT/GO/epoxy coating showing a well-dispersed and enhanced barrier properties.